2006
DOI: 10.1159/000090430
|View full text |Cite
|
Sign up to set email alerts
|

What Characterizes Substance Abusers Who Commit Suicide Attempts? Factors Related to Axis I Disorders and Patterns of Substance Use Disorders

Abstract: Objective: The frequency of suicide attempts and clinical characteristics of attempters among poly-substance abusers and alcoholics were examined. Methods: A consecutive sample (n = 260) of in- and outpatients from two Norwegian counties were assessed by Composite International Diagnostic Interview (Axis I disorders), Millon’s Clinical Multiaxial Inventory (Axis II disorders) and the Norwegian National Client Assessment Form. When analysing the association between suicide attempters and the range of predictor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 57 publications
(49 reference statements)
2
25
2
3
Order By: Relevance
“…As indexed by most scoring highly on the AUDIT, it appears the level of hazardous and harmful drinking is quite high among this group of patients. Studies from Northern America and Scandinavia suggest that non-psychotic patients with mood, anxiety and or personality disorders are prone to alcohol induced problems (Cantor-Graae, Nordstrom, & McNeil, 2001;Dawson, Grant, Stinson, & Chou, 2005;Landheim, Bakken, & Vaglum, 2006). There are suggestions that these patients consider the consumption of alcohol as 'self-medication.'…”
Section: Discussionmentioning
confidence: 99%
“…As indexed by most scoring highly on the AUDIT, it appears the level of hazardous and harmful drinking is quite high among this group of patients. Studies from Northern America and Scandinavia suggest that non-psychotic patients with mood, anxiety and or personality disorders are prone to alcohol induced problems (Cantor-Graae, Nordstrom, & McNeil, 2001;Dawson, Grant, Stinson, & Chou, 2005;Landheim, Bakken, & Vaglum, 2006). There are suggestions that these patients consider the consumption of alcohol as 'self-medication.'…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many studies found that polydrug use or combination of alcohol and another drug increase the risk of suicidal behavior (Bohnert, Roeder, & Ilgen, 2010;Darke & Ross, 2002;Darke, Ross, Lynskey, & Teesson, 2004;Delisle, 2009;Landheim, Bakken, & Vaglum, 2006;Mino et al, 1999;Preuss et al, 2002). A meta-analysis estimates standardized mortality ratios (SMR 1 ) for suicide as follows: alcohol use disorder (SMR = 979), opioid use disorder (SMR = 1351) and polydrug use (SMR = 1685) (Wilcox, Conner, & Caine, 2004).…”
Section: Hypotheses To Explain the Prevalence Of Suicidal Behaviorsmentioning
confidence: 99%
“…Many studies have been conducted to examine risk factors for adolescent suicide. Most adolescent risk models for suicide contain ''traditional'' risk factors such as depression or substance use (Docksai 2009;Landheim et al 2006;Méan et al 2005). However, other possible factors such as body dissatisfaction or risky sexual behaviors have lacked adequate research and evaluation in general, even though these factors have been prevalent among adolescents and associated with risk factors for suicide (Barker and Galambos 2003;Goode 2001).…”
Section: Demographic Variables and Suicidementioning
confidence: 99%